Statistical Yearbook 2018 - Republic of Bulgaria. National Statistical Institute (NSI); A. Ilkova (Sofia: NSI, 2019)
b
GENERAL REVIEW -- I. Basic indicators about the demographic, social and economic development of the Republic of Bulgaria for the 2001 - 2017 period -- II. Territory, surface area and climate -- III. Environment -- IV. Population and demographic processes -- V. Labour market -- VI. Household income, expenditure and consumption -- VII. National accounts -- VIII. Prices -- IX. Investments -- X. Finance -- XI. Exports and imports of goods -- XII. Energy -- XIII. Non-financial enterprises -- XIV. Agriculture -- XV. Forestry -- XVI. Industry -- XVII. Construction -- XVIII. Transport -- XIX. Domestic trade; Accommodation and food service activities -- XX. Tourism --XXI. Health -- XXII. Education -- XXIII. Research and development activity and innovation -- XXIV. Culture and art -- XXV. Criminality and justice -- REGIONAL REVIEW -- Methodological notes -- I. General characteristics and territorial division -- II. Population -- III. Labour market -- IV. Household income and expenditure -- V. Regional accounts -- VI. Investments -- VII. Non-financial enterprises -- VIII. Agriculture -- IX. Industry -- X. Construction -- XI. Transport -- XII. Domestic trade; Accommodation and food service activities -- XIII. Tourism -- XIV. Health -- XV. Education -- XVI. Culture and art -- XVII. Criminality and justice -- INTERNATIONAL REVIEW -- Methodological notes -- I. Surface area and population -- II. Environment -- III. Labour market -- IV. Prices -- V. Exports and imports -- VI. Agriculture -- VII. International tourism -- VIII. Health -- IX. Education -- X. Culture and art -- XI. International comparisons.
Keywords: Statistics - Bulgaria